Lower barriers to primary care after the implementation of the Affordable Care Act in the United States of America - Arturo Vargas Bustamante; Jie Chen (Pan American Health Organization, 2018)
Objective. To examine short-term changes in perceived barriers to access to primary care before and after implementation of the Affordable Care Act (ACA) among adults in the United States of America. Methods. The ACA was approved in 2010. We used the National Health Interview Survey (NHIS) for the years 2011-2014 to compare the main reported problems in accessing primary care among adult respondents in 2011-2013 (before implementation of mandatory ACA health insurance for individuals) and in 2014 (after that implementation). A multivariate logistic stepwise regression analysis was used to identify trends with primary care barriers. Results. We found that from 2010 through 2014, individuals were progressively less likely to report challenges to accessing care, such as having trouble finding a provider, getting accepted as new patients, and health care providers not accepting their health insurance. In addition, adults were less likely to report inconveniences linked to waiting times for an appointment and with provider's office hours. Conclusions. Informing policymakers, providers, and system administrators about the short-term changes in perceived barriers to care offers a baseline for evaluating policies and programs linked to implementing the ACA, as well as assessing how prepared primary care networks were for the influx of newly insured patients. Nevertheless, the abolition of the ACA health insurance mandate through legislation approved in December 2017 has put into question whether patients' perceptions of improved access to care will be sustained in the future.